MODEL PERSEDIAAN PROBABILISTIK YANG MEMUAT VARIABEL LEAD TIME DENGAN PENDEKATAN DISTRIBUSI NORMAL - Nopriadi '; T. P. Nababan; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article  discusses how to minimize total inventory cost of probabilistic model (Q,r) where condition of back order and crashing lead time are allowed. Normal distribution approach is used when the demand during the lead time is normally distributed. Themodel is used to determine when the order is made (r) and how much the quantity Q to be ordered to minimize the total cost of inventory.